2022
DOI: 10.3389/fcvm.2021.783872
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Promotes Interaction Between Endothelin-Dependent EDNRA/EDNRB and Myocardin-SRF to Regulate Pathological Vascular Remodeling

Abstract: IntroductionPathological vascular remodeling is a hallmark of various vascular diseases. Smooth muscle cell (SMC) phenotypic switching plays a pivotal role during pathological vascular remodeling. The mechanism of how to regulate SMC phenotypic switching still needs to be defined. This study aims to investigate the effect of Andrographolide, a key principle isolated from Andrographis paniculate, on pathological vascular remodeling and its underlying mechanism.MethodsA C57/BL6 mouse left carotid artery complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…PDA, a derivative of andrographolide, has been clinically used for the therapeutic treatment of inflammatory diseases. Our previous studies demonstrated that andrographolide plays a critical role in maintaining vascular homeostasis, as well as in regulating smooth muscle cell phenotypic switch-dependent pathological vascular remodeling [ 26 , 27 ]. However, whether PDA is involved in regulating endothelial barrier repair in pathological vascular remodeling is not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PDA, a derivative of andrographolide, has been clinically used for the therapeutic treatment of inflammatory diseases. Our previous studies demonstrated that andrographolide plays a critical role in maintaining vascular homeostasis, as well as in regulating smooth muscle cell phenotypic switch-dependent pathological vascular remodeling [ 26 , 27 ]. However, whether PDA is involved in regulating endothelial barrier repair in pathological vascular remodeling is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse carotid arteries were fixed with 4% paraformaldehyde overnight at 4 °C and embedded in paraffin, and 5 μm thick slides were collected. H&E staining was performed as previously described [ 27 ]. For IHC staining, antigen retrieval was performed with citric acid treatment at 98 °C for 5 to 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spheroid sprouting assay was performed as described previously (37). Methylcellulose solution was prepared by dissolving 6 g methylcellulose (sigma) in 250 ml prewarmed serum-free medium, and 250 ml complete medium was added.…”
Section: Spheroid Sprouting Assaymentioning
confidence: 99%